PENGARUH PEMBELAJARAN ETIKA DAN LINGKUNGAN AKADEMIK TERHADAP SENSITIVITAS ETIS MAHASISWA AKUNTANSI - Yeyen Gustriana; Darman Usman (Jurnal Akuntansi, 2017)
The aim of this research is to know the implementation of etchic learning and academic environment at the university of Bengkulu. This study predicted the implementation of business etchic learning which based on integrated business ethic subject, lecturer’s knowledge, and learning method which would improve the sensitivity of university student. In addition, this study also predicted other factors which influenced the ethic sensitivity of university student, there is an academic environment which described from lecturer and student’s interaction and student interaction with the other student. This research is empirical research with a quantitatif approach that involves the use of statistical analysis, this research uses primary data. The tool used in this research is multiple linear regressions with SPSS version 16. The results showed that the variables of lecturer’s knowledge and learning method have a positive influence on the ethical sensitivity of accounting students. Variables ethic subject, lecturer interaction and student interaction are not proved an effect on the ethical sensitivity of accounting students.Keywords : ethic learning, ethic sensitivity, academic environment.